Рецепція Тaраса Шевченка в часописі «Biuletyn Polsko-Ukraiński» - Яручик, Ольга Борисівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зосереджено увагу на рецепції творчості одного з найвидатніших митців слова у світовій літе-ратурі Тараса Шевченка у варшавському ілюстрованому тижневику міжвоєнного періоду «Biuletyn Polsko-Ukraiński». Авторка намагається підкреслити важливу роль, яку відіграв «Biuletyn» у тогочасних польсько-українських стосунках (30-ті роки ХХ ст.).In the article concentrated attention on the reception of one creation of the most prominent thinkers of word in world literature of Tarasa Shevchenko in the Warsaw weekly illustrated paper of «Biuletyn Polsko-ukrainski» in an intermilitary period. Attention reviews is spared on new editions of poet, to the articles about his creation and his value for development of ukrainsko-polʼskikh literary mutual relations. «Biuletyn Polsko-ukrainski» on the pages published many reasons from history of Ukraine, presented Ukrainian literature the Polish reader with a purpose most full to acquaint Polish society with Ukrainian literary and cultural life, and also heroic history of the Ukrainian state system. Does an author try to underline an important role which was played by «Biuletyn Polsko-ukrainski « in the of that time Polish-Ukraine relations (the 30-th of XX century).
Keywords: польсько-українські взаємини; співпраця; творчість; переклади; критика